Selective Qur'anic Lexical Clustering as a Pedagogical Framework for Adult Arabic Reading Instruction - Mizan Sakroni; Wildana Wargadinata; Mamluatul Hasanah (Al-Muyassar: Journal of Arabic Education, 2026)
This study examines selective Qur'anic lexical clustering as a pedagogical framework for adult Arabic reading instruction at Majelis Ta'lim Al-Ma'uun, Sidoarjo. The analysis focuses on three clusters: high-frequency vocabulary, familiarity and novelty, and prefixes and suffixes. Using a qualitative case-study design, data were collected through classroom observation, semi-structured interviews with the teacher, adult learners, and the program manager, and learning documents. The data were analyzed through reduction, display, and conclusion drawing, while credibility was strengthened through source, technique, and time triangulation. The findings show that high-frequency clustering helps adult learners identify recurrent function words such as prepositions, pronouns, and conjunctions; familiarity-novelty clustering allows the teacher to connect previously learned vocabulary with newly introduced items; and prefix-suffix clustering enables learners to recognize verbal forms, subject markers, and word endings in Qur'anic verses. The novelty of this article lies in proposing selective Qur'anic lexical clustering as a practical pedagogical framework for organizing vocabulary in adult reading instruction, combining vocabulary frequency, meaningful prior knowledge, and Arabic morphological awareness.